Influência dos procedimentos abrasivos sobre a microdureza, rugosidade superficial e alteração de massa de diferentes compósitos - Amaral, Fabrício Reskalla [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This in vitro study was conducted to evaluate qualitatively and quantitatively the microhardness, roughness and mass change of conventional composites Filtek Z350XT (3M ESPE), Esthet-X HD (DENTSPLY), Grandio (VOCO) and composite resins bulk-fill Surefill SDR (DENTSPLY) and X-tra fill (VOCO), after polishing and chemical and mechanical degradation . Hundred cylindrical samples, twenty for each material (10,0 mm in diameter x 4.0 mm in thickness) were prepared . After light cured, all samples were stored at a relative humidity of 100% for 24 hours at 370C for further steps towards the finish and surface polishing sandpaper d'water granulation 600, 800, 1200, 2500 and 4000, Sof Lex discs and felt impregnated with alumina at a speed of 600rpm in polishing. The specimens were randomly divided in 2 groups: control group (CG) and test group (TG). The specimens were evaluated for roughness, hardness and weight change in two phases: control group (CG) after the storage period and test group (TG) after immersion in acid solution (Coca Cola®) and abrasion test simulated toothbrushing . To analyze the Knoop hardness was used microdurometer Shimadzu HMV-G 21, operating at a load of 200 g for 15 seconds . To evaluation the surface roughness used the contact profilometer (Mitutoyo Surftest-301 model, with Ra measurement parameter, and to evaluate mass alteration used an electronic scale Shimadzu AY 220 with precision 0,0002g. The erosive challenge was performed with the use of drink Coca Cola®, for a period of 30 days, the drink changed daily and its pH measured in all exchanges. Since the mechanical degradation was evaluated after simulated toothbrushing using toothpaste Colgate Triple Action, and samples submitted to 100,000 brushing cycles. the results obtained by two-way ANOVA and post hoc Scheffé test by (p <0.05). Showed... (Complete abstract electronic access below)

O presente estudo in vitro foi realizado com o objetivo de avaliar qualitativamente e quantitativamente a microdureza, a rugosidade e alteraçāo de massa de resinas compostas convencionais Filtek Z350XT (3M ESPE), Esthet X-HD (DENTSPLY), Grandio (VOCO) e resinas compostas bulk-fill Surefill SDR (DENTSPLY) e X-Trafill (VOCO), após polimento e desafio químico e mecânico. Foram confeccionados 20 corpos-de-prova (cp) para cada um dos materiais descritos anteriormente, com formato cilíndrico (10,0 mm de diâmetro X 4,0 mm de altura). Após fotopolimerizados, todos os corpos de prova foram armazenados em umidade relativa de 100% por 24h a 370C para posterior realização do acabamento e polimento de superfície através de lixas d'água com granulação 600, 800, 1200, 2500 e 4000, disco de óxido de alumínio e feltro impregnado com alumina, na velocidade de 600rpm em politriz. Os espécimes foram divididos de forma aleatória, em 2 grupos distintos: grupo controle (GC) e grupo teste (GT). Os espécimes foram avaliados quanto a rugosidade, alteraçāo de massa e dureza em dois momentos: grupo controle (GC) após o período de armazenamento e grupo teste (GT) após imersão em solução ácida (Coca Cola®) e teste de abrasão por escovaçāo simulada. Para análise da microdureza Knoop, utilizou-se microdurômetro SHIMADZU HMV-G 21, com carga de 200g por 15s. Para avaliar a rugosidade superficial utilizou-se o rugosímetro de contato (Mitutoyo modelo surftest-301, com parâmetro de medição Ra e para avaliar alteraçāo de massa utilizou-se uma balança eletrônica Shimadzu AY 220 com precisão de 0,0002g. O desafio erosivo foi realizado com a utilização de bebida da marca Coca Cola®, por um período de 30 dias, sendo a bebida trocada diariamente e seu pH aferido em todas as trocas...(Resumo completo clicar acesso eletrônico abaixo)